Welcome to Westonci.ca, where you can find answers to all your questions from a community of experienced professionals. Join our platform to connect with experts ready to provide precise answers to your questions in different areas. Explore comprehensive solutions to your questions from knowledgeable professionals across various fields on our platform.

What is the inverse of the function f(x) = x +3?

h(x)=1/3x + 3
h(x)=1/3x - 3
h(x)= x - 3
h(x)= x + 3


Sagot :

Step-by-step explanation:

the inverse function simply calculate the original x it of a given y. so, we need to transform the original function to calculate x instead of y.

and then, at the end to make it a formally correct function definition, we rename x to y and y to x.

y = x + 3

x = y - 3

=> to make it a formally correct function definition

y = x - 3 = h(x)